PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS (TGT) TERHADAP PEMAHAMAN KONSEP PECAHAN SISWA KELAS IV SD - Suhernilawati; Kusuma, Rendra Sakbana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the Teams Games Tournaments learning model on understanding the concept of fractions for class IV students of UPTD SDN Sepulu 1. The method in this research is a quantitative method with a Pre-Experimental research design in the from of a one group design. And the sample used in this research was 22 class IV students of UPTD SDN Sepulu 01. The research instrument was a test of students’ understanding of learning. Meanwhile, the analysis tests in this research are validity test, reliability test, normality test, and paired sample t-test with the help of the IBM SPSS v21.0 application. Based on the results of the paired sample t-test analysis, the Sig value was obtained. (2-tailed) 0.000 < 0.05 which shows the influence of the Teams Games Tournaments (TGT) learning model on understanding the concept of fractions for class IV students of UPTD SDN Sepulu 1.